Babesia microti from humans and ticks hold a genomic signature of strong population structure in the United States. (December 2016) - Carpi, Giovanna; Walter, Katharine; Mamoun, Choukri; Krause, Peter; Kitchen, Andrew; Lepore, Timothy; Dwivedi, Ankit; Cornillot, Emmanuel; Caccone, Adalgisa; Diuk-Wasser, Maria
Abstract Background Babesia microti is an emerging tick-borne apicomplexan parasite with increasing geographic range and incidence in the United States. The rapid expansion ofB. microti into its current distribution in the northeastern USA has been due to the range expansion of the tick vector, Ixodes scapularis, upon which the causative agent is dependent for transmission to humans. Results To reconstruct the history ofB. microti in the continental USA and clarify the evolutionary origin of human strains, we used multiplexed hybrid capture of 25B. microti isolates obtained fromI. scapularis and human blood. Despite low genomic variation compared with other Apicomplexa, B. microti was strongly structured into three highly differentiated genetic clusters in the northeastern USA. Bayesian analyses of the apicoplast genomes suggest that the origin of the current diversity ofB. microti in northeastern USA dates back 46 thousand years with a signature of recent population expansion in the last 1000 years. Human-derived samples belonged to two rarely intermixing clusters, raising the possibility of highly divergent infectious phenotypes in humans. Conclusions Our results validate the multiplexed hybrid capture strategy for characterizing genome-wide diversity and relatedness ofB. microti from ticks and humans. We find strong population structure inB. microti samples from the Northeast indicating potential barriers to gene flow.